Bioestratigrafía de las pizarras ordovícicas en la Sierra deTamames (Sinclinal de Sequeros-Ahigal de los Aceiteros, prov. Salamanca) - Gutiérrez Marco, Juan Carlos; Rábano, Isabel (Coloquios de Paleontología, 1983)
Trilobites, graptolites, brachiopods and mollusks collected in fou.r localities of the unity inforinally named as« La Bastida Shales» are studied, in ages ranging between Lower Llanvirn and Lower Llandeilo. The biostratigraphical study allows cori-date tbis uaity with other similar Formatioris of the Central-Iberian Zone. New findings of graptolites in [he Silurian sucression of the Sequeros synrline indicate, for the flrst time, a Lower Llandovery age (triangulatus to ruagnus. Zones) [nr the lower portion ot the unity discordant over tbo Ordovicia.n shales.